THE EFFECT OF HEALTH EDUCATION REGARDING PREVENTION OF PULMONARY TUBERCULOSIS TRANSMISSION TO KNOWLEDGE AND ATTITUDES OF COMMUNITY - Khoirun Nisa, Nurul; Siagian, Basirum; Pratama, Rika Yuanita; Sunarti, Sunarti (Universitas Airlangga, 2024)
Introduction: Tuberculosis (TB) is an infectious disease that is a major cause of poor health and one of the leading causes of death worldwide. Pulmonary tuberculosis or often referred to as pulmonary TB is an infectious disease that is still endemic in society. The purpose of this study was to determine the knowledge and attitudes of the community regarding preventing the transmission of pulmonary tuberculosis. Methods: This used a quantitative design with a pre-experimental approach, using a convenience sampling technique with a sample size of 40 respondents. The research was conducted at the Community of Nanga Pemubuh Village, Sekadau Regency. This research data collection used a questionnaire measuring instrument. The analysis used was a Paired Sample T-test and Wilcoxon test with a significance level of É‘<0.05. The variables involved in this research were health education, knowledge, and attitudes. Results: The statistical test results were obtained at knowledge p value = 0.004 and attitude p value = 0.013, meaning that statistically health education had a significant effect on increasing community knowledge and attitudes before and after education about preventing the transmission of tuberculosis in Nanga Pemuhuh Village, Sekadau. Conclusions: Health education regarding preventing the transmission of pulmonary tuberculosis has a significant effect on increasing public knowledge and attitudes. Increasing knowledge and attitudes about preventing the transmission of tuberculosis after outreach is expected to be able to reduce the prevalence rate of tuberculosis.